The Comparison of Satisfaction, Commitment, and Performance Between Female and Male Students - Hazriyanto; Hendri Kremer; Badaruddin Ibrahim; Nasruji; Vincentius Ade Arianto Ciptoputra (LPPM Undiksha, 2024)
Education in higher education is a concern for many parties, especially related to the output of students from these universities. Various problems arise in the process of producing student outcomes that are by the demands of the times. The results in the form of student achievement and performance are very helpful for universities to reach their goals. Development, acceleration, and improvement of human resource output are the main concerns, especially in the Galileo College of Economics (STIE). This research focuses on student satisfaction, commitment, and performance. This research is a quantitative study involving 185 students as respondents. The purpose of this study is to see the comparison of satisfaction, commitment, and performance between male and female students. The research data was collected using a questionnaire, and processed with Amos SEM statistics. The results of the multi-group comparative analysis show that there is a positive and significant influence between satisfaction, commitment, and performance of women and men. The findings in this study found that satisfaction with women's performance is the same and insignificant. For this reason, the campus needs to pay attention to student satisfaction, commitment, and performance. For future research, it is necessary to consider other variables not examined in this study, such as the environment, and comparisons between students in universities. In conclusion, achievement is the result of work that a person achieves both in terms of quality and quantity in doing work by the responsibilities given to him.